2017
DOI: 10.1038/ncomms13925
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate response decay and defense metabolite accumulation contributes to age-regulated dynamics of plant insect resistance

Abstract: Immunity deteriorates with age in animals but comparatively little is known about the temporal regulation of plant resistance to herbivores. The phytohormone jasmonate (JA) is a key regulator of plant insect defense. Here, we show that the JA response decays progressively in Arabidopsis. We show that this decay is regulated by the miR156-targeted SQUAMOSA PROMOTER BINDING PROTEIN-LIKE9 (SPL9) group of proteins, which can interact with JA ZIM-domain (JAZ) proteins, including JAZ3. As SPL9 levels gradually incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(170 citation statements)
references
References 70 publications
6
163
0
1
Order By: Relevance
“…Therefore, Li and his co-workers in 2015 have demonstrated that nta-eTMX27 inhibits the expression and function of nta-miRX27 which targets mRNA of quinolinate phosphoribosyl transferase 2 (QPT2) genes leading to enhanced nicotine biosynthesis in the topping treated tobacco. The most recent report by Mao et al (2017) shows the regulatory role of miR156 targeting SPL9 in the biosynthesis of glucosinolates, which are secondary metabolites functioning as defense metabolites against insect herbivores and pathogens. The SPL9 interacts with JA ZIM-domain (JAZ) proteins, including JAZ3 to control jasmonate synthesis.…”
Section: The Role Of Mirnas In the Regulating Biosynthesis Of Alkaloimentioning
confidence: 99%
“…Therefore, Li and his co-workers in 2015 have demonstrated that nta-eTMX27 inhibits the expression and function of nta-miRX27 which targets mRNA of quinolinate phosphoribosyl transferase 2 (QPT2) genes leading to enhanced nicotine biosynthesis in the topping treated tobacco. The most recent report by Mao et al (2017) shows the regulatory role of miR156 targeting SPL9 in the biosynthesis of glucosinolates, which are secondary metabolites functioning as defense metabolites against insect herbivores and pathogens. The SPL9 interacts with JA ZIM-domain (JAZ) proteins, including JAZ3 to control jasmonate synthesis.…”
Section: The Role Of Mirnas In the Regulating Biosynthesis Of Alkaloimentioning
confidence: 99%
“…The identification of a direct interaction between PhSPL17 and PhJAZ1 at the protein level provides us with new insight to resolve both issues (Fig. ), as it is already known that SPL can stabilize the JAZ protein by competing with COL1 . This research avenue will be prominent in our upcoming research work.…”
Section: Discussionmentioning
confidence: 79%
“…SQUAMOSA promoter binding protein‐like transcription factors (SPLs) are targeted by miR156 to regulate secondary metabolite production and jasmonate (JA) responses in plants. Accordingly, we identified one SPL family member (PhSPL17) from moso bamboo whose expression pattern correlated strongly with the on‐ and off‐year cycle of bamboo . However, PhSPL17 was not regulated by exogenous JA .…”
Section: Introductionmentioning
confidence: 94%
“…This indicates that cross between BoZ and BrK would be helpful in creating B. napus with higher glucosinolate content. As reported, the glucosinolates in Arabidopsis and Brassica crops were transported from maternal tissues (e.g., leaves; Nour‐Eldin & Halkier, ; Nour‐Eldin et al, ), and glucosinolates in leaves have been proved with functions in improving stress tolerance, insect and pathogen resistance (Davila Olivas et al, ; Mao et al, ; Xu et al, ). The linoleic acid was greatly increased in all the hybrids but in diploid parents, indicating better oil composition in resynthesized B. napus .…”
Section: Discussionmentioning
confidence: 83%